Analysis of the Effect of Tapioca Flour Adhesive on the Characteristics of Palm Oli Empty Charcoal Briquettes - Muhammad Anhar Pulungan; Sihar Siahaan; Siti Maretia Benu (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Palm oil solid waste such as oil palm empty fruit bunches (TKKS) if not processed can be explained by the environment. This study attempts to study the utilization of oil palm empty fruit bunches as charcoal briquettes. Charcoal briquettes are one of the alternative fuels to replace fuel gas and firewood charcoal. The empty sign of the oil palm is burned so that it becomes charcoal, then the charcoal is ground and sifted, after being sifted it is given a mixture of adhesive, namely tapioca flour. The mixed charcoal is put into a briquette press. The research was conducted on a laboratory scale with a carbonization process at a temperature of 500℃, carbonization time of 3 hours. The process of drying briquettes at a temperature of 100⁰C for 1 hour. Comparison of the composition of 1000 grams of empty oil palm fruit bunches with 20% tapioca starch adhesive. From the results of the study, the briquette values obtained were as follows: 4775.18 cal/g, 6.96% water, 9.18% ash content, and 84 minutes of burning time. The empty bunches of charcoal briquettes were tested according to the SNI No.1/6235/2000 standard, which is a minimum calorific value of 5000 cal/gram, a maximum water content of 8%, and an ash content of 8%. The parameters of water content and burn time have met the standard. The parameters of the ash content and calorific value of the samples taken and tested have not met the standard of SNI No.1/6235/2000. One of the steps that can be tried to improve the quality of the ash content and calorific value is to rearrange the composition of the adhesive.